A anencefalia fetal e o aborto na Evangelium Vitae do Papa João Paulo II - Silva, Adriano Corrêa da (2012)
Amid the various threats that human life is, the Catholic Church cools further its mission inherited by Christ to proclaim the Gospel of Life to the universality of the people, for she firmly believes that human life, even when marked by weaknesses, and even by physical or mental disabilities, pre-and postnatal, is always a splendid gift of God to be protected. This is the horizon of the defense of human life, and more precisely, the cases of fetal anencephaly, that their dissertation converges to evidence in the light of Christian revelation, but also through interdisciplinarity, that human life is a fundamental principle and primary among all values between different cultures. Therefore, the first chapter is about an expression often used by John Paul II - "culture of life" - which, in turn, must be cultivated and propagated throughout the world as the center of the message proclaimed by Christ and his Church as delegated depository of Evangelium Vitae and in time in the history of mankind, for man alive is the first and fundamental way for the Church. For this purpose, the respective chapter discusses the aspect of biblical-theological conception of human life and human being. In the second chapter, in contrast to the first, is the explanation of the terminology - "culture of death" - since there are numerous signs that arise to threaten human life, and nascent human life, God-given as a gift. And one of the threats to human dignity still in its early uterine culture is the death of abortion legislation that attempts to expand worldwide, including in the current Brazilian Congress, to include cases of fetal anencephaly. Finally, the third chapter, such as character conclusion reaffirms the defense of human life as a task and responsibility that must be taken not only by the Church of Christ, but for all people of good will as a way to go before a question of survival of humanity itself, which must be awakened, increasingly, develop an ethical principle against the defense of human life, especially the helpless intra-uterine life